Method for inhibiting metal chlorine corrosion by using metal oxyacid radical anions and application of metal oxyacid radical anions
By using metal oxylate ions in electrolytic seawater to form polymetallic acid clusters, the corrosion problem of metal electrodes caused by chloride ions in seawater is solved, and efficient protection of metal electrodes is achieved, which is suitable for a variety of industrial scenarios.
Patent Information
- Application Number
- CN202411353345.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The high content of chloride ions in seawater causes electrochemical corrosion of metal materials during electrolysis of seawater, limiting the application of electrolytic seawater technology.
Metal oxygenate ions are used to form polymetal oxygenate anion clusters. Through electrostatic repulsion, specific adsorption and steric hindrance effects, the chloride ion concentration on the surface of the metal electrode is reduced and chlorine corrosion is alleviated.
It effectively reduces the electrochemical corrosion rate of metal electrodes, extends the service life of the electrodes, and is suitable for metal corrosion protection in seawater electrolysis, offshore facilities and various industrial scenarios.
Smart Images

Figure CN119287379A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal corrosion and protection, and particularly relates to a method for using metal oxyacid anions to inhibit metal chloride corrosion and an application thereof. Background Art
[0002] Currently, freshwater resources are relatively scarce. In comparison, seawater resources are abundant and easily accessible. More than 97.5% of the world's water resources are seawater, so seawater is considered an "inexhaustible" resource. Due to the high concentration of ions in seawater, it can easily damage the structure of metal materials that come into contact with seawater. - It is the ion with the highest content in seawater (about 0.5M). Due to its small radius, strong diffusion ability, high electronegativity, and strong complexing ability, it can easily accelerate the chemical and electrochemical corrosion of metal materials. Therefore, chlorine corrosion is the main and most serious type of corrosion involved in seawater corrosion.
[0003] Seawater electrolysis is a common method for fully developing seawater resources. However, chlorine corrosion causes electrochemical corrosion of the metal electrodes used in seawater electrolysis, restricting the application of seawater electrolysis technology. Summary of the Invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes the use of metal oxyacid ions for inhibiting chemical corrosion and electrochemical corrosion of metals by chloride-containing solutions. The metal oxyacid ions form polymetallic oxyacid anion clusters during chemical corrosion, electrolysis or electrochemical corrosion. The polymetallic oxyacid anion clusters can alleviate metal chloride corrosion (such as seawater chloride corrosion) in situ. When used in seawater electrolysis, they can alleviate electrochemical corrosion of metal electrodes used, and have good application prospects.
[0005] The invention also provides an electrolyte for alleviating metal corrosion.
[0006] The present invention also provides an electrolysis system.
[0007] The present invention also provides a method for alleviating corrosion of metal electrodes.
[0008] In a first aspect of the present invention, metal oxyacid ions are proposed to inhibit chemical corrosion or electrochemical corrosion of metals by chloride-containing solutions.
[0009] Metal oxyacid anion clusters are formed during chemical corrosion, electrolysis or electrochemical corrosion. Due to the specific chemical adsorption of metal oxyacid anion clusters on the surface of metal electrodes or metal substrates, the metal oxyacid anion clusters react with Cl - The electrostatic repulsion and steric hindrance effect are formed between the two surfaces, and the present invention can achieve low interface Cl -Concentration, alleviate the chloride corrosion of metal electrodes. Specifically, metal oxyacid anion monomers and polymetallic oxyacid anion clusters repel chloride ions (Cl) at the metal-chloride solution (e.g. electrolyte) interface through electrostatic interaction. - ), which reduces the chlorine corrosion rate; oxygen-containing acid anions are adsorbed on the metal surface through surface specificity to form a passivation layer, which reduces the diffusion rate of chlorine at the metal-chlorine-containing solution (such as electrolyte) interface, hinders the occurrence of the binding process between chlorine and metal sites, and reduces the chlorine corrosion rate; the ionic radius of the polyoxyacid anion cluster is relatively large, and due to its strong steric hindrance effect, it can reduce the Cl at the metal-chlorine-containing solution (such as electrolyte) interface. - concentration, reducing the chlorine corrosion rate.
[0010] Furthermore, metal oxygen-containing acid ions can be applied to seawater corrosion protection of equipment in direct contact with seawater in closed systems such as seawater desalination facilities, offshore wind power platforms, offshore oil and gas platforms, and offshore construction platforms; they can be used in offshore areas to couple with offshore photovoltaic and wind power generation systems to achieve large-scale production of green hydrogen energy; they can be used for seawater corrosion protection of metal components in scenarios such as railways, airports, highway bridges, port terminals, water conservancy projects, ships, airplanes, trains, coal industry, power systems, urban water supply, seawater aquaculture, cultural relics, seawater desalination, marine new energy, offshore platforms and equipment, submarine pipelines, marine oil equipment, construction, automobiles, oil and gas industry, metallurgy, electronics industry, papermaking industry, chemical industry, telecommunications, home appliances, pharmaceutical industry, mining industry, food processing, medical equipment, and agriculture.
[0011] In some embodiments of the present invention, the chlorine-containing solution contains Cl - , Cl in chlorine-containing solution - The concentration is 0.1~5mol / L.
[0012] In some embodiments of the present invention, the pH of the chlorine-containing solution ranges from 0 to 14.
[0013] In some embodiments of the present invention, the chlorine-containing solution includes seawater, simulated seawater, industrial electrolyte or tap water.
[0014] In some embodiments of the present invention, the metal element in the metal oxyacid ion includes at least one of chromium, molybdenum or tungsten. Alternatively, the metal oxyacid ion includes at least one of molybdate, chromate or tungstate.
[0015] In some embodiments of the present invention, the initial concentration of metal oxoacid ions in the chlorine-containing solution is 0.01-6 mol / L, optionally 0.05-4 mol / L, calculated as metal atoms.
[0016] In some embodiments of the present invention, the temperature of the chlorine-containing solution is 10-90°C, optionally 20-80°C.
[0017] In some embodiments of the present invention, a corrosion inhibitor containing metal oxyacid ions is added to a chlorine-containing solution to protect a metal electrode or a metal substrate during electrochemical corrosion or chemical corrosion.
[0018] In some embodiments of the present invention, the metal oxyacid ions are used in the electrolyte of seawater electrolysis to protect metal electrodes from corrosion.
[0019] Through the above embodiment, metal oxyacid ions will form polymetallic oxyacid anion clusters during the seawater electrolysis process. Due to the specific chemical adsorption of polymetallic oxyacid anion clusters on the surface of the metal electrode and the reaction with Cl - The electrostatic repulsion and steric hindrance effect can reduce the interfacial Cl - Concentration, alleviate the chloride corrosion of metal electrodes. Specifically, it includes: adding metal oxygenates to the electrolyte, and blocking the close contact between corrosive ions and the protected metal by forming polymetallic oxygenate anion clusters in situ on the metal surface, thereby alleviating seawater chloride corrosion: (1) Interface specific adsorption, polymetallic oxygenate ions such as polymolybdate can form specific adsorption on the surface of the metal electrode, and gather in situ on the electrode surface to play an anti-corrosion role. (2) Inter-ionic electrostatic repulsion, polymolybdate anion clusters can form charge repulsion on other negatively charged anions, reduce the concentration of anions on the electrode surface, and thus produce an anti-chloride ion corrosion effect on the electrode surface. (3) The steric hindrance effect of polyacids, the center, side edges and bottom edges of the polymolybdate anion cluster structure are usually distributed with molybdenum atoms and oxygen atoms. The large steric hindrance can inhibit the approach of chloride anions to the electrode surface, thereby producing an anti-corrosion effect.
[0020] In some embodiments of the present invention, the protected or guarded metal includes at least one of Ni, Mo, Fe, Co, Ti or Au.
[0021] In some embodiments of the present invention, the metal electrode includes one or more of Ni, Raney nickel, NiMo alloy, NiFe alloy, Co metal, CoFe alloy or Au.
[0022] In some embodiments of the present invention, the metal substrate includes one or more of Ni, NiMo alloy, NiFe alloy, Co metal, CoFe alloy or Au.
[0023] In some embodiments of the present invention, a corrosion inhibitor containing metal oxyacid ions is added to a chlorine-containing solution for protecting a metal electrode or a metal substrate during electrochemical corrosion or chemical corrosion, wherein the raw materials of the chlorine-containing solution include but are not limited to Cl-containing - The raw materials of the chlorine-containing solution include one or more natural / artificial corrosive liquids selected from seawater, simulated seawater, industrial electrolyte, industrial wastewater or tap water. - At least one of seawater, simulated seawater, industrial electrolyte, industrial wastewater or tap water.
[0024] In some embodiments of the present invention, the corrosion inhibitor includes at least one of molybdate, chromate or tungstate.
[0025] In some embodiments of the present invention, the molybdate includes at least one of sodium molybdate, potassium molybdate, ammonium molybdate or ammonium heptamolybdate.
[0026] The role of the above molybdate includes the formation of heptamolybdate or octamolybdate in the corrosion microenvironment, through the specific chemical adsorption of polymolybdenum oxyacid anion clusters on the surface of the metal electrode, and the reaction with Cl - The electrostatic repulsion and steric hindrance effect between the two reduce the interfacial Cl - concentration, alleviating metal chloride corrosion.
[0027] In some embodiments of the present invention, the chromate includes at least one of sodium chromate, potassium chromate, magnesium chromate or ammonium chromate.
[0028] In some embodiments of the present invention, the tungstate includes at least one of sodium tungstate, potassium tungstate or ammonium tungstate.
[0029] In some embodiments of the present invention, the electrochemical reaction includes a seawater electrolysis reaction.
[0030] In some embodiments of the present invention, metal oxoacid ions are used to protect layered double hydroxides of oxygen evolution reaction catalysts, oxygen evolution reaction catalysts, chlorine evolution reaction catalysts, metal substrates of oxygen evolution reaction, metal substrates of chlorine evolution reaction, or alkaline anion exchange membrane electrolysis cells. The electrochemical reactions that can occur in alkaline anion exchange membrane electrolysis cells include oxygen evolution reaction, chlorine evolution reaction, and the like.
[0031] The above-mentioned method of using metal oxygen-containing acid radical ions to inhibit the electrochemical corrosion of metals can be used to inhibit the electrochemical corrosion of electrocatalytic electrodes in chloride-containing electrolytes, can achieve high stability in the application of seawater electrolysis catalysts, can be used for corrosion protection of common oxygen evolution reaction catalyst layered double hydroxides, can be used for corrosion protection of oxygen evolution reaction catalysts and chlorine evolution reaction catalysts and substrates, can be used for corrosion protection of seawater electrolysis hydrogen production electrodes and corresponding electrolytic cells. Specifically, the above-mentioned method of alleviating metal electrode corrosion can achieve in-situ alleviation of metal chloride corrosion by polymetallic oxygen-containing acid radical anion clusters, which can effectively reduce the Cl on the metal surface from three aspects: ion electronegativity repulsion, specific adsorption, and steric hindrance. - This method effectively protects metals from chlorine corrosion in simulated seawater and real seawater electrolytes with different pH concentrations. In particular, in alkaline anion exchange membrane electrolyzers for industrial hydrogen production from seawater, this method also provides good corrosion protection for metal catalyst electrodes and substrates. At the same time, this method has a wide range of applicability and can be used in a wide range of Cl - The present invention can provide corrosion protection for Ni metal, NiMo alloy, NiFe alloy, Co metal, CoFe alloy, Au metal, etc. in corrosive media with a concentration and pH range. Optionally, the anion concentration of the corrosion inhibitor involved in some embodiments of the present invention is also adjustable within a concentration range of 0.05 to 4 mol / L, which is conducive to the efficient utilization of seawater resources in multiple scenarios.
[0032] In a second aspect of the present invention, an electrolyte capable of alleviating metal corrosion is proposed, wherein the electrolyte comprises chloride ions (Cl - ), and also includes at least one of a metal oxo ion or a polymetallic oxo anion cluster.
[0033] The electrolyte capable of alleviating metal corrosion according to the embodiments of the present invention has at least the following beneficial effects:
[0034] During the electrochemical corrosion process of metal, hydroxide at the metal-electrolyte solution interface is consumed. The electrolyte of the present invention can in situ induce metal oxyacid anion monomers to form polymetallic oxyacid anion clusters. - The electrostatic repulsion between the metals, the specific adsorption on the metal surface, and the steric hindrance of the metals themselves improve the resistance of the electrode material surface to chlorine corrosion, and can effectively alleviate the corrosion of various metal materials in chlorine-containing solutions (such as seawater) over a wide pH range and temperature range. The electrolyte capable of alleviating metal corrosion of the present invention is a method for in-situ construction of polymetallic oxoacid anion clusters to alleviate metal chloride corrosion (such as seawater chloride corrosion).
[0035] In some embodiments of the present invention, the metal elements in the metal oxo ions and the polymetallic oxo anion clusters are independently selected from at least one of chromium, molybdenum or tungsten.
[0036] In some embodiments of the present invention, the metal oxyacid ion includes at least one of molybdate, chromate or tungstate.
[0037] In some embodiments of the present invention, the polymetallic oxoacid anion cluster includes at least one of heptamolybdate, octamolybdate, chromate, dichromate, heptotungstate, decatungstate, and dodecatungstate.
[0038] In some embodiments of the present invention, the sum of the initial concentrations of the metal oxo ions and the polymetallic oxo anion clusters in the electrolyte, calculated as metal atoms, is 0.01-6 mol / L, and can be optionally 0.05-4 mol / L.
[0039] In some embodiments of the present invention, the electrolyte contains Cl - , Cl - The concentration of the hydroxybenzoic acid in the electrolyte is 0.1-5 mol / L, and can be optionally 0.5-1.25 mol / L.
[0040] In some embodiments of the present invention, the pH range of the electrolyte is 0-14.
[0041] In some embodiments of the present invention, the temperature of the electrolyte is 10-90°C, optionally 20-80°C.
[0042] In some embodiments of the present invention, the raw materials for preparing the electrolyte include a corrosion inhibitor, and the corrosion inhibitor includes metal oxyacid ions.
[0043] In some embodiments of the present invention, the corrosion inhibitor includes at least one of molybdate, chromate or tungstate.
[0044] In some embodiments of the present invention, the molybdate includes at least one of sodium molybdate, potassium molybdate, ammonium molybdate or ammonium heptamolybdate.
[0045] In some embodiments of the present invention, the chromate includes at least one of sodium chromate, potassium chromate, magnesium chromate or ammonium chromate.
[0046] In some embodiments of the present invention, the tungstate includes at least one of sodium tungstate, potassium tungstate or ammonium tungstate.
[0047] In some embodiments of the present invention, the raw materials for preparing the electrolyte solution further include any other material raw materials required according to the electrolysis requirements. Optionally, the raw materials for preparing the electrolyte solution further include aqueous fluid.
[0048] In some embodiments of the present invention, the aqueous fluid includes, but is not limited to, deionized water, seawater, tap water, some industrial wastewater, and other aqueous liquids. The seawater may be simulated seawater or natural seawater. Alternatively, the aqueous fluid includes at least one of natural seawater, simulated seawater, industrial electrolyte, industrial wastewater, or tap water.
[0049] In some embodiments of the present invention, the raw materials for preparing the electrolyte further include at least one of an alkaline substance or an electrolyte substance.
[0050] In some embodiments of the present invention, the alkaline substance includes but is not limited to at least one of sodium hydroxide, potassium hydroxide, etc. Alternatively, the alkaline substance includes at least one of sodium hydroxide or potassium hydroxide.
[0051] In some embodiments of the present invention, the electrolyte material comprises a metal chloride.
[0052] In some embodiments of the present invention, the metal chloride comprises at least one of sodium chloride or potassium chloride.
[0053] According to electrolysis requirements, the electrolyte may further include other electrolysis additives.
[0054] A third aspect of the present invention provides an electrolysis system comprising the above-mentioned electrolyte.
[0055] In some embodiments of the present invention, the electrolysis system includes a seawater electrolysis hydrogen production electrolysis cell.
[0056] In some embodiments of the present invention, the seawater electrolysis hydrogen production electrolytic cell includes a working electrode, and the working electrode includes at least one of Ni, Fe, Co, or Au. Alternatively, the working electrode may be one or more of Ni metal, NiMo alloy, NiFe alloy, Co metal, CoFe alloy, or Au metal.
[0057] In some embodiments of the present invention, the seawater electrolysis hydrogen production electrolytic cell comprises an alkaline electrolyzer or an alkaline anion exchange membrane electrolyzer. Optionally, an anion exchange membrane electrolyzer assembled from nickel metal can achieve stable operation for over 800 hours.
[0058] In a fourth aspect of the present invention, a method for alleviating corrosion of metal electrodes is proposed, comprising the following steps: placing the metal electrode in a chlorine-containing electrolyte for electrolysis, wherein the chlorine-containing electrolyte includes the electrolyte described in any one of the second aspects of the present invention.
[0059] Through the above embodiment, during the electrochemical corrosion process of the metal, hydroxide consumption occurs at the metal-electrolyte solution interface, and metal oxyacid anion monomers are in situ induced to form polymetallic oxyacid anion clusters. - The electrostatic repulsion between the metals, the specific adsorption on the metal surface and the steric hindrance effect of the metals themselves improve the resistance of the electrode material surface to chlorine corrosion, and can effectively alleviate the corrosion of various metal materials in chlorine-containing solutions (such as seawater) within a wide pH range and a wide temperature range. It is a method for in situ construction of polymetallic oxyacid anion clusters to in situ alleviate metal chloride corrosion (such as seawater chloride corrosion).
[0060] This method is applicable to metal corrosion at open circuit potential or applied anodic potential, especially for protection against seawater corrosion and chlorine corrosion of metals. Specifically, it can be applied to mitigate chlorine corrosion of metals or alloys such as Ni metal, NiMo alloy, NiFe alloy, Co metal, CoFe alloy, and Au metal.
[0061] Specifically, optionally, in some embodiments of the present invention, the method can be adapted to alleviate electrochemical corrosion under applied potential or open circuit potential in an electrolyte composed of deionized water, simulated seawater, real seawater, KOH, and NaOH in the pH range of 0-14 and the temperature range of 20-80°C. At the same time, the concentration of the corrosion-inhibiting anion involved in the method is also adjustable within the concentration range of 0.05-4 mol / L. For the electrochemical corrosion process under applied anodic potential, the method can be successfully applied to alkaline electrolytic cells and alkaline anion exchange membrane devices. This method induces metal oxyacid anions to generate polymetallic oxyacid anion clusters in situ by utilizing the process of anodic electrochemical corrosion consuming hydroxide, and utilizes the electrostatic repulsion, interface-specific adsorption, and steric hindrance effect of the two types of ions to reduce the chloride ion concentration at the metal-electrolyte solution interface, thereby effectively reducing the metal chloride corrosion rate. It is a metal corrosion protection technology suitable for a wide pH range, a wide temperature range, and a variety of solution environments.
[0062] In some embodiments of the present invention, the pH range of the chlorine-containing electrolyte is 0 to 14, such as 7 to 14. Optionally, the pH value of the microenvironment at the interface between the metal electrode and the electrolyte is 0 to 6.
[0063] In some embodiments of the present invention, the temperature of the chlorine-containing electrolyte is 10-90°C, optionally 20-80°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0065] Figure 1 Mo7O in the electrolyte of Example 1 of the present invention 246- Schematic diagram of cluster structure;
[0066] Figure 2 The accelerated aging test time-potential curves of the nickel electrodes in the electrolytic cells of Example 1 and Comparative Examples 1-4 of the present invention are shown;
[0067] Figure 3 The scanning polarization curves and key corrosion parameter test results of the nickel electrode in the electrolytic cell in electrolytes S1 and D1 are shown;
[0068] Figure 4 Graph showing changes in nickel electrode surface morphology during the electrolyte accelerated aging experiment in Example 1 of the present invention and Comparative Example 1;
[0069] Figure 5 Statistical graph of the percentage of nickel electrode corrosion areas during the electrolyte accelerated aging test in Example 1 of the present invention and Comparative Example 1;
[0070] Figure 6 Graph showing the test results of ion electrostatic repulsion during accelerated aging experiments of the electrolytes of Example 1 and Comparative Example 1 of the present invention;
[0071] Figure 7 Graph showing the test results of ion electrostatic repulsion during chronovoltametry testing at different current densities for the electrolytes of Example 1 and Comparative Examples 1 and 4 of the present invention;
[0072] Figure 8 Graph showing in-situ Raman signal test results at different current densities for the electrolyte of Example 1 of the present invention;
[0073] Figure 9 Graph showing the test results of specific adsorption of ions during accelerated aging experiments of the electrolytes of Example 1 and Comparative Example 4 of the present invention;
[0074] Figure 10 This is a graph showing the test results of the chlorine atomic percentage on the electrode surface during the accelerated aging experiment of the electrolyte in Example 1 of the present invention and Comparative Examples 1, 3, and 4;
[0075] Figure 11 This is a graph showing the in-situ Raman signal test results of polymolybdate ions in the electrolyte of Example 2 of the present invention;
[0076] Figure 12 This is a diagram showing the response effect of the presence of molybdenum to pH in an electrolyte in which molybdenum is used as an additional element for metal oxyacids according to the present invention;
[0077] Figure 13 The present invention is an electrolyte solution with pH = 3, 5, 7, 9 when the molybdenum exists in the form and content distribution diagram;
[0078] Figure 14This is a graph showing the in-situ Raman signal test results of polymolybdate ions in the electrolyte of Example 3 of the present invention;
[0079] Figure 15 This is a graph showing the temperature universality test results of the method for in-situ mitigation of metal chloride corrosion by polymetallic oxoacid anion clusters in an electrolyte according to an embodiment of the present invention;
[0080] Figure 16 This is a time-potential curve of the accelerated aging test of the nickel electrode in the electrolytic cell in Example 4 of the present invention and Comparative Example 1;
[0081] Figure 17 Graph showing the response of the molybdenum form to pH in an electrolyte having a molybdenum concentration of 0.4 mol / L according to the present invention;
[0082] Figure 18 Graph showing the stability test results of the electrolyte S8 in Example 6 of the present invention and the electrolyte D5 in Comparative Example 5 in an alkaline anion exchange membrane electrolysis cell;
[0083] Figure 19 Graph showing the test results of the chlorine corrosion resistance of the electrolyte S1 of Example 1 of the present invention and the electrolyte D1 of Comparative Example 1 to iron-doped nickel hydroxide;
[0084] Figure 20 This is a graph showing the test results of the potential decay rate and performance decay rate of iron-doped nickel hydroxide in the electrolyte S1 of Example 1 of the present invention and the electrolyte D1 of Comparative Example 1. DETAILED DESCRIPTION
[0085] The following will clearly and completely describe the concept and technical effects of the present invention in conjunction with the embodiments to fully understand the purpose, features and effects of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0086] The experimental methods in the following examples, for which specific conditions are not specified, are generally performed in accordance with conventional conditions in the art or conditions recommended by the manufacturers; the raw materials and reagents used, unless otherwise specified, are all commercially available from conventional markets.
[0087] Example 1
[0088] This embodiment discloses an electrolyte (electrolyte S1), the preparation process of which includes:
[0089] Weigh 4.04 g of sodium hydroxide, 7.30 g of sodium chloride, and 3.09 g of sodium molybdate solid, add deionized water to dissolve, and transfer to a 100 mL volumetric flask to adjust the volume to obtain electrolyte S1, wherein the concentration of molybdenum (existing in the form of molybdenum and polymolybdate anions) calculated as molybdenum atoms is 0.15 mol / L, and the pH is 14.
[0090] This embodiment also discloses an electrolysis system comprising an electrolytic cell, comprising a circular glass cell, an electrolyte S1 therein, and a three-electrode system. The three-electrode system is formed in the circular glass cell, using a treated nickel electrode as a working electrode, a graphite rod as a counter electrode, and Hg / HgO as a reference electrode. Each electrode is placed in the electrolyte S1, forming the three-electrode system.
[0091] Among them, the pretreatment steps of the nickel electrode include: cutting a piece of foam nickel (size 30mm×10mm×0.5mm), first placing it in 1.0mol / L hydrochloric acid for 40 minutes to remove the surface oxide layer, and then washing the residual hydrochloric acid on the surface with deethanol and deionized water to obtain the treated nickel electrode.
[0092] Example 2
[0093] This embodiment discloses an electrolyte (electrolyte S2), the preparation process of which includes:
[0094] Weigh 0.404 g of sodium hydroxide, 7.30 g of sodium chloride, and 3.09 g of sodium molybdate solid, add deionized water to dissolve, and transfer to a 100 mL volumetric flask to make up the volume to obtain a test electrolyte S2, in which the concentration of molybdenum (in the form of molybdate and polymolybdate anions) calculated as molybdenum atoms is 0.15 mol / L, and the pH is 12.
[0095] This embodiment further discloses an electrolysis system, which differs from the embodiment 1 only in that the electrolyte S2 prepared in this embodiment is used to replace the electrolyte S1 in the embodiment 1.
[0096] Example 3
[0097] This embodiment discloses an electrolyte (electrolyte S3), the preparation process of which includes:
[0098] Weigh 0.0404 g of sodium hydroxide, 7.30 g of sodium chloride, and 3.09 g of sodium molybdate solid, add deionized water to dissolve, and transfer to a 100 mL volumetric flask to make up the volume to obtain a test electrolyte S3, in which the concentration of molybdenum (in the form of molybdate and polymolybdate anions) calculated as molybdenum atoms is 0.15 mol / L, and the pH is 8.
[0099] This embodiment also discloses an electrolysis system comprising an electrolytic cell comprising an electrolyte S3 and a three-electrode system. A treated nickel electrode serves as a working electrode, a platinum wire serves as a counter electrode, and a solid silver / silver chloride serves as a reference electrode. Each electrode is placed in the electrolyte S3 to form a three-electrode system in an in-situ Raman electrolytic cell. The electrolyte and ambient temperature are room temperature (20°C). The pretreatment steps for the nickel electrode are the same as those in Example 1.
[0100] Example 4
[0101] This embodiment discloses a series of electrolytes (electrolytes S4 to S6). The difference between electrolytes S4 to S6 and electrolyte S1 in Example 1 is that the molybdenum concentration calculated as molybdenum atoms is different. The molybdenum concentrations calculated as molybdenum atoms in electrolytes S4 to S6 are 10 mmol / L, 50 mmol / L, and 150 mmol / L, respectively.
[0102] This embodiment also discloses a series of electrolysis systems, which differ from embodiment 1 only in that electrolytes S4 to S6 prepared in this embodiment are used to replace electrolyte S1 in embodiment 1 respectively.
[0103] Example 5
[0104] This embodiment discloses an electrolyte (electrolyte S7), which differs from the electrolyte S1 in Example 1 in that the molybdenum concentration calculated as molybdenum atoms is different. The molybdenum concentration calculated as molybdenum atoms in the electrolyte S7 is 0.4 mol / L.
[0105] This embodiment further discloses an electrolysis system, which differs from the embodiment 1 only in that the electrolyte S7 prepared in this embodiment is used to replace the electrolyte S1 in the embodiment 1.
[0106] Example 6
[0107] This embodiment discloses an electrolyte (electrolyte S8), the preparation process of which includes:
[0108] Seawater, sodium hydroxide and sodium molybdate are mixed to obtain electrolyte S8. The concentration of sodium hydroxide in electrolyte S8 is 1 mol / L, the concentration of molybdenum in terms of molybdenum atoms is 0.15 mol / L, and the concentration of Cl - The concentration is about 0.5 mol / L.
[0109] This embodiment discloses an electrolysis system comprising an alkaline anion exchange membrane electrolytic cell, the electrolytic cell comprising the electrolyte S8 prepared in this embodiment. In this embodiment, the anion exchange membrane is used as an ion transport channel and gas isolation barrier. A nickel metal electrode, after undergoing the pretreatment steps described in Example 1, is composited with the anion exchange membrane and assembled into the alkaline anion exchange membrane electrolytic cell. The electrolytic cell is a two-electrode (working electrode, counter electrode) system that can be connected to an electrochemical workstation to form a complete voltage and current loop. Chronopotentiometry can be used for stability testing, for example, by setting the constant current parameter to 1A.
[0110] Example 7
[0111] This embodiment discloses an electrolysis system, which differs from Example 1 in that this embodiment uses a layered double hydroxide catalyst electrode (size 30 mm × 10 mm × 0.5 mm) instead of the nickel electrode in Example 1. The layered double hydroxide catalyst electrode can be a catalyst for the oxygen evolution reaction and a catalyst for the chlorine evolution reaction.
[0112] Comparative Example 1
[0113] This comparative example discloses an electrolyte (electrolyte D1), the preparation process of which comprises: weighing 4.04 g of sodium hydroxide and 7.30 g of sodium chloride, dissolving them in deionized water, and transferring them to a 100 mL volumetric flask to adjust the volume to obtain electrolyte D1 (wherein the concentration of NaOH is 1 mol / L, and the concentration of NaCl is 1.25 mol / L).
[0114] This comparative example also discloses an electrolysis system, which differs from Example 1 only in that the electrolyte D1 prepared in this comparative example is used to replace the electrolyte S1 in Example 1.
[0115] Comparative Example 2
[0116] This comparative example discloses an electrolyte (electrolyte D2), the preparation process of which includes: weighing 4.04g of sodium hydroxide, 7.30g of sodium chloride, and 1.27g of sodium nitrate solid, dissolving them in deionized water, and transferring them to a 100mL volumetric flask to make up the volume to obtain a test electrolyte D2, wherein the concentration of nitrogen element (present in the form of nitrate anions) is 0.15mol / L.
[0117] This comparative example also discloses an electrolysis system, which differs from Example 1 only in that the electrolyte D2 prepared in this comparative example is used to replace the electrolyte S1 in Example 1.
[0118] Comparative Example 3
[0119] This comparative example discloses an electrolyte (electrolyte D3), the preparation process of which includes: weighing 4.04g of sodium hydroxide, 7.30g of sodium chloride, and 2.13g of sodium sulfate solid, adding deionized water to dissolve, and transferring to a 100mL volumetric flask to make up the volume to obtain a test electrolyte D3, wherein the concentration of sulfur element (present in the form of sulfate anions) is 0.15mol / L.
[0120] This comparative example also discloses an electrolysis system, which differs from Example 1 only in that the electrolyte D3 prepared in this comparative example is used to replace the electrolyte S1 in Example 1.
[0121] Comparative Example 4
[0122] This comparative example discloses an electrolyte (electrolyte D4), the preparation process of which includes: weighing 4.04g of sodium hydroxide, 7.30g of sodium chloride, and 2.46g of sodium phosphate solid, adding deionized water to dissolve, and transferring to a 100mL volumetric flask to make up the volume to obtain a test electrolyte D4, wherein the concentration of phosphorus element (present in the form of phosphate anion) is 0.15mol / L.
[0123] This comparative example also discloses an electrolysis system, which differs from Example 1 only in that the electrolyte D4 prepared in this comparative example is used to replace the electrolyte S1 in Example 1.
[0124] Comparative Example 5
[0125] This comparative example discloses an electrolyte (electrolyte D5), which differs from Example 6 in that: the electrolyte D5 does not contain molybdate. Specifically, the preparation process of the electrolyte D5 includes: taking seawater and sodium hydroxide, mixing them, and obtaining the electrolyte D5. The concentration of sodium hydroxide in the electrolyte D5 is 1 mol / L, and the concentration of Cl - The concentration is about 0.5 mol / L.
[0126] This comparative example discloses an electrolysis system including an alkaline anion exchange membrane electrolysis cell, which differs from Example 6 only in that the electrolyte D5 in this comparative example is used instead of the electrolyte S8 in Example 6.
[0127] Test example
[0128] This test example conducted performance tests on the electrolytes and electrolysis systems of the embodiments and comparative examples, specifically including:
[0129] 1. Build an electrochemical corrosion research system and conduct accelerated aging experiments:
[0130] The three-electrode system of the electrolysis system of each embodiment and comparative example is connected to the electrochemical workstation to construct a complete voltage and current loop to build an electrochemical corrosion research system, wherein the electrolyte and ambient temperature are room temperature (20°C). The constant current parameter of the chronopotentiometry is set to 1A, and an accelerated aging test is carried out. The change of the system potential over time is recorded to explore the effect of each electrolyte (such as the oxygen-containing acid radical ions corresponding to the four elements of nitrogen, sulfur, phosphorus, and molybdenum) on the improvement of the metal's resistance to chlorine corrosion.
[0131] In order to better illustrate the effect of oxygen-containing acid radical ions on the improvement of metal's resistance to chloride corrosion, the molybdate ion (MoO4 2- ) and the reaction equilibrium and equilibrium constant between polymolybdate ions (see Table 1 below). 2- Depending on the environment, it will spontaneously transform into different configurations, such as heptamolybdate (Mo7O 24 6- ) or octamolybdate (Mo8O 26 4- ). In the corrosion process induced by open circuit potential or applied anodic potential, H near the electrode surface + As the concentration increases, MoO4 2- Polymolybdate cluster ions are formed by polymerization in an electrolytic environment.
[0132] Table 1 Ionic equations for polymolybdate conversion
[0133]
[0134] Figure 1 Mo7O 24 6- Schematic diagram of the cluster structure, which is one of the forms of molybdenum in the electrolyte S1, Mo7O 24 6- There are three types of molybdenum atomic sites: M1 at the center, M2 on the side edges, and M4 at the bottom. There are six types of O atomic sites: O1 to O6 in the figure. When polymolybdate ions are used in the electrolysis of chloride-containing solutions, they produce a steric hindrance effect. Molybdenum and oxygen atom species are distributed at the center, side edges, and bottom of the polymolybdate anion cluster. The significant steric hindrance inhibits chloride ions and other negative ions from approaching the electrode surface, resulting in an anti-corrosion effect.
[0135] Figure 2The potential-time curves for each accelerated aging experiment are shown. Electrodes placed in different electrolytes exhibited different stability times at the anodic potential for accelerated corrosion. The test duration indicates the strength of the anions in the electrolyte in inhibiting chloride corrosion of the metal. In electrolyte D1, which lacks oxyanions, the metal electrode failed after one hour of stable operation (due to chloride corrosion). Using electrolyte D1 as a blank control, electrolytes containing oxyanions (i.e., electrolytes D2-D4 and S1) exhibited varying degrees of corrosion inhibition, improving the metal electrode's resistance to chloride corrosion. Compared to electrolyte D1, the stability of nickel metal in electrolytes D2 and D3 was slightly longer than one hour, indicating that nitrate and sulfate exhibited weak inhibition. In electrolyte D4, which contained 0.15 mol / L phosphate, the electrode's stability was extended to nearly two hours (double the duration of the blank control), demonstrating the strong inhibition of phosphate. In the electrolyte S1 with a molybdenum content of 0.15 mol / L, the electrode can operate stably for 8 hours and exhibits obvious resistance to chlorine corrosion in the electrolyte S1. Figure 1 , Molybdenum is Mo7O 24 6- exists in the corrosion microenvironment, so Figure 2 The results shown illustrate the effectiveness of the strategy of in-situ alleviation of metal chloride corrosion by the polymetallic oxoacid anion cluster proposed in the present invention, that is, the excellent role of molybdate and polymolybdate ions in electrode anti-chlorine corrosion.
[0136] Figure 3 The scanning polarization curves and key corrosion parameters of nickel electrodes in electrolytes S1 and D1 are shown. pit Indicates the pitting potential of the electrode. Compared with electrolyte D1, in electrolyte S1, the nickel electrode E pit The increase in the electrochemical resistance from 0.267V to 0.527V, indicating that pitting corrosion is less likely to occur, indicates that the polymolybdate ions in electrolyte S1 significantly enhance the nickel electrode's resistance to chloride corrosion. Simultaneously, the Tafel slope of the pitting process in electrolyte S1 increases from 50.99mV / dec to 79.60mV / dec, demonstrating the effectiveness of the proposed polymetallic oxoacid anion cluster strategy for in-situ chloride corrosion mitigation.
[0137] Table 2 Summary of key parameters of nickel electrode corrosion in electrolyte
[0138] electrolyte Epit(V) Tafel slope (mV / dec) Electrolyte S1 0.527 79.60 Electrolyte D1 0.267 50.99
[0139] Figure 4 In order to accelerate the change of nickel electrode surface morphology during the aging experiment, the surface morphology of the nickel electrode was observed in situ during the accelerated aging experiment. The black shadow area on the electrode that appeared as the anode potential increased was the corrosion area. Figure 4 It can be seen that the corrosion of the metal electrode in the electrolyte S1 is significantly suppressed. Figure 4 As can be seen from the above figure, the surface corrosion of the metal electrode gradually deepens with the increase of the applied potential in the simulated seawater electrolyte. However, when using electrolyte S1, the polymetallic oxyacid anion clusters contained therein can be in-situ anti-corrosion, and the metal electrode can maintain good corrosion resistance at different potentials or current densities. The electrolyte of the present invention can be used in scenarios where metals are protected from seawater chlorine corrosion under high current density conditions. During the electrolysis process of metal electrodes in seawater environments, the oxidative corrosion activity of metal electrodes is higher at higher electrolysis voltages or current densities. In important fields such as renewable energy coupled with seawater electrolysis to produce hydrogen, the anti-corrosion strategy of the present invention using an electrolyte containing polymetallic oxyacid anion clusters can be well applied to 500-1000mA cm -1 The high current density is much higher than the current application level (200-300mA cm -1 ), which is expected to promote the industrialization of seawater electrolysis with high current density and achieve cost reduction and efficiency improvement.
[0140] Figure 5 The percentage of corrosion area in the accelerated aging test of nickel electrodes is statistically analyzed. Figure 4 The figure shows a quantitative description of the changes in the nickel electrode surface morphology during the accelerated aging experiment. For electrolyte D1, when the anode voltage exceeded 1.58V vs. RHE, the nickel electrode corrosion area reached 5%. When the voltage increased to 1.88V vs. RHE, the nickel electrode corrosion area accounted for over 60%. When the voltage increased to 2.18V vs. RHE, nearly 80% of the electrode surface was corroded. In contrast, in electrolyte S1, the electrode corrosion area remained close to 0 as the voltage increased from 1.08V to 2.18V vs. RHE, indicating that no corrosion occurred on the electrode surface. The introduction of the polymetallic oxoacid ion strategy in electrolyte S1 significantly inhibited electrode corrosion.
[0141] Figure 6 Demonstrates electrostatic repulsion of polymolybdate ions ( Figure 6The horizontal axis is the time when the accelerated aging experiment started). In the accelerated aging experiment with the applied anodic potential, an oxygen evolution reaction occurs at the anode, and ethylenediaminetetraacetic acid anions are added instantaneously to the electrolyte. Since the oxidation potential of ethylenediaminetetraacetic acid anions is lower than that of the anodic oxygen evolution reaction, the electrode potential is instantaneously reduced when ethylenediaminetetraacetic acid anions are added. In this test example, ethylenediaminetetraacetic acid anions of the same amount of substance are added to different electrolytes (electrolyte D1 and electrolyte S1) at the same time. The potential in electrolyte D1 drops by 20mV, and the potential in electrolyte S1 drops by only 6mV. This is because the electrostatic repulsion between the molybdenum species and the ethylenediaminetetraacetic acid anions hinders the diffusion process of the ions to the electrode surface, reducing the electrode potential drop caused by the oxidation reaction of the ethylenediaminetetraacetic acid anions, illustrating the electrostatic repulsion of polymolybdate.
[0142] In addition, the parameter of small molecule oxidation potential difference △E (mV) is introduced to explain the electrostatic repulsion of polymetallic oxoacid anion clusters. Figure 7 As shown in the figure, chronopotentiometry tests were conducted at different current densities in a molybdate-containing electrolyte (electrolyte S1), a phosphate electrolyte (electrolyte D4), and a background electrolyte (electrolyte D1). When equal amounts of small molecule organic oxides (ethylenediaminetetraacetic acid) were instantaneously added to the different electrolytes, the smaller the potential change △E (mV), the smaller the effect of the addition of small molecule organic matter on the original oxidation reaction, that is, the stronger the anti-corrosion repellency of the electrode surface under the original electrolyte working condition. Figure 7 It can be seen that (MoE, PE, and BE represent the test results of electrolyte S1, electrolyte D4, and electrolyte D1, respectively) the potential difference △E of different electrolytes does not change significantly at a small current density. As the current density increases to 600, 700, and 1000 mA cm -1 It can be clearly observed that the △E change value in the electrolyte containing molybdate is smaller than that in the control group under high current density. Figure 8 The in-situ Raman signals of molybdate and polymolybdate ions in electrolyte S1 at different current densities can be explained together. The current range in the figure is 800-1000 mA cm -1 A Raman peak corresponding to polymolybdate ions appeared at 940 wavenumbers, indicating that polymetallic oxoacid anion clusters were generated in situ on the metal electrode surface at high current density, significantly improving the electrode's corrosion resistance. Furthermore, the steric hindrance of polymetallic oxoacid anions is the primary factor in improving the electrode's corrosion resistance under high current conditions.
[0143] Figure 9The specific adsorption of polymolybdate ions was demonstrated. After the accelerated aging test, the electrode deep-section X-ray photoelectron spectroscopy test was performed on the nickel electrode surface at 0nm and 5nm respectively to detect the molybdenum and phosphorus element signals. In the electrolyte S1, a molybdenum element signal was detected at 0nm on the electrode surface, but no molybdenum element signal was detected at 5nm, indicating that molybdenum was specifically adsorbed on the electrode surface (see Figure 9 In electrolyte D4, no phosphorus signal was detected at 0nm and 5nm, indicating that phosphorus did not undergo specific adsorption on the electrode surface (see Figure 9 lower middle picture).
[0144] Figure 10 The chlorine atomic percentages on the electrode surface and deep section after 30 minutes of accelerated aging tests in electrolytes D1, D3, D4, and S1 are shown, illustrating the chlorine exclusion effect caused by the specific adsorption of polymolybdate ions. X-ray photoelectron spectroscopy was used to observe the Cl - Concentration. Figure 10 It can be seen that in electrolyte D1, Cl on the electrode surface - The atomic percentage is nearly 20%, indicating that the electrode has undergone severe chlorine corrosion. In electrolyte D3, the atomic percentage of chlorine on the electrode surface and 5nm deep section is lower than that in electrolyte D1, indicating that the sulfate anion in electrolyte D3 has a certain degree of inhibitory effect on the chlorine corrosion of the nickel electrode. In electrolyte D4, a low content of Cl was detected at 0nm on the electrode surface. - , Cl was hardly detected at a depth of 5 nm - This indicates that phosphate has a more significant Cl - However, chlorine corrosion still occurred on the electrode surface. In electrolyte S1, no Cl was detected on the electrode surface or in the 5nm deep section. - , indicating that the electrode did not undergo chloride corrosion, demonstrating the effectiveness of the strategy of polymetallic oxoacid anion clusters proposed in the present invention to alleviate metal chloride corrosion in situ.
[0145] Figure 11 The in-situ Raman signal of polymolybdate ions in electrolyte S2 (pH = 12). The current density first increases and then decreases with time. The in-situ Raman test results show that molybdate ions (corresponding to 896 cm -1 Raman vibration) exists in the electrolyte and increases when the current density increases to 200-500 mA cm -2 In the interval, polymolybdate ions appear (corresponding to 940cm -1 Raman vibration). As the current density of the anodic oxygen evolution reaction increases, OH -The increased consumption rate leads to a decrease in the local pH near the electrode, inducing the in situ formation of polymolybdate clusters. When the current density decreases, the pH on the electrode surface quickly returns to the alkaline environment of the bulk electrolyte, and the polymolybdate signal disappears, indicating that the formation of polymolybdate ion clusters is a reversible process.
[0146] Figure 12 Based on the polymolybdate ion conversion equation and conversion equilibrium constant, the relationship between the existence form of molybdate ions and the relative percentage content in response to the solution pH is calculated. Specifically, the following is a graph showing the response effect of the existence form of molybdenum in a molybdenum-containing solution with a molybdenum concentration of 0.15 mol / L in terms of molybdenum atoms to pH. The total molybdenum concentration in each solution is 0.15 mol / L. The upper left graph shows the distribution of the percentage of molybdenum in molybdate and polymolybdate with respect to pH. When pH>7, molybdenum is almost completely converted to MoO4 2- As the pH decreases, the form of molybdenum gradually changes. When the pH is lower than 6.5, Mo7O 24 6- Oxygen-containing acid radical clusters are generated. When the pH is around 5, molybdenum is mainly in the form of Mo7O 24 6- When the pH continues to drop below 4, molybdenum is converted to molybdenum through hydrogen heptamolybdate (HMo7O 24 5- ) is converted into Mo8O 26 4- The upper right picture shows the Mo7O 24 6- With HMo7O 24 5- Simplified to Mo7O 24 6- The response effect of the percentage of molybdenum in molybdate and polymolybdate on pH when the molybdenum content is a single ion. The lower left and lower right figures respectively show the response relationship between the concentration of the molybdate and polymolybdate ions and pH. The present invention illustrates the response relationship between polymetallic oxoanions and environmental pH, and further illustrates that in situ pH changes on the electrode surface can regulate the formation of in situ polymetallic acid anion clusters. The above figures all illustrate that in an alkaline environment, molybdenum is mostly in the form of MoO4 2- As the pH decreases, H + As the concentration increases, molybdate aggregates into polymolybdate ions. Figure 11 For the nickel anode in the accelerated aging experiment, oxygen evolution reaction occurs on the electrode surface and consumes OH - The pH value near the electrode surface is reduced. At the same time, during the electrochemical corrosion process under open circuit voltage, there will be a local pH reduction and the induction of polymolybdate ions. This illustrates the feasibility of the present invention of using the electrochemical corrosion process to in situ induce polymolybdate clusters to achieve seawater corrosion protection of metals.
[0147] 2. Build an in-situ electrochemical corrosion research system and conduct accelerated aging experiments:
[0148] An in-situ electrochemical corrosion research system was constructed, including: placing a treated nickel electrode (treatment steps are the same as in Example 1) as a working electrode, a platinum wire as a counter electrode, and solid silver / silver chloride as a reference electrode in each electrolyte (electrolyte S1 and S3), respectively, to form a three-electrode system in an in-situ Raman electrolytic cell, and the electrolyte and ambient temperature were room temperature (20°C).
[0149] Accelerated aging experiment: The obtained three-electrode system was connected to the electrochemical workstation to build a complete voltage and current loop. The constant current parameters of the chronopotentiometry were set with an experimental period of 500 seconds. The current magnitude applied at different time points was recorded. At the same time, the 850-1000 cm -1 The Raman signal of the interval.
[0150] Figure 13 Based on the polymolybdate ion conversion equation and conversion equilibrium constant, the relationship between the existence form and relative percentage of molybdate ions in response to solution pH is calculated, specifically: Molybdenum existence form and content distribution at pH = 3, 5, 7, and 9. According to the equilibrium constant of the mutual conversion reaction between different molybdenum existence forms, in a strongly acidic environment of pH = 3, molybdenum is mainly converted into Mo8O 26 4- A small amount of molybdenum exists in the form of HMo7O 24 5- In the weakly acidic environment of pH=5, molybdenum exists in the form of Mo7O 24 6- exists in the form of HMo7O 24 5- In a neutral solution at pH=7, MoO4 2- It is the main form of molybdenum. When the concentration of molybdenum increases to 4 mol / L (calculated as molybdenum atoms), part of MoO4 2- Polymerization to Mo7O 24 6- In an alkaline environment with pH=9, molybdenum is converted into MoO4 2- exists in the form of .
[0151] Figure 14 This is the in-situ Raman signal of polymolybdate ions in electrolyte S3 (pH = 8). When the current density increases to 100-150 mA cm -2 When Mo7O 24 6-The signal indicates that the in-situ metal chloride corrosion mitigation method of polymetallic oxoacid anion clusters is applicable to the electrolyte with pH=8. Figure 11 The signal disappears when the current density decreases. When the pH decreases from 12 to 8, the anodic oxidation current that induces the production of polymolybdate ions also decreases accordingly, indicating the dependence of polymolybdate formation on the pH of the electrode surface microregion.
[0152] Figure 8 、 Figure 11 、 Figure 14 This indicates that the in-situ metal chloride corrosion mitigation method using polymetallic oxoacid anion clusters is applicable to electrolytes with a wide pH range.
[0153] In an electrolytic system where the solution pH is always maintained above 7, the in-situ chlorine corrosion inhibition strategy of the polymetallic oxoacid anion cluster proposed in this invention is still significantly effective: in an electrolytic system, the observation of solution pH can be divided into two parts: bulk pH and interface pH. The corrosion of the metal electrode occurs in the microenvironment of the contact interface between the metal and the electrolyte. Figure 8 、 Figure 11 、 Figure 14 As shown in Figure 1, the in-situ Raman signal detection diagram of polymolybdate in the electrolysis system under different pH conditions (pH = 8, 12, 14) is provided. - Consumption of metal ions causes changes in the pH of the electrode surface microenvironment, inducing the in situ formation of polymetallic oxoate anion clusters on the electrode surface to protect the metal from chloride ion corrosion. The bulk pH of the solution remains high and does not change significantly before and after electrolysis, demonstrating the wide pH range applicability of the polymetallic oxoate anion cluster in situ method for alleviating chloride corrosion of metals.
[0154] 3. Temperature universality test:
[0155] The three-electrode systems of each electrolysis system from Example 4 and Comparative Example 1 were connected to an electrochemical workstation, establishing a complete voltage and current loop to create an electrochemical corrosion research system. Accelerated aging experiments were conducted at 20°C, 40°C, 60°C, and 80°C. The chronopotentiometry constant current parameter was set to 1A, and accelerated aging tests were performed. The change in system potential over time was recorded to investigate the effect of the electrolyte at 20-80°C on the metal's resistance to chlorine corrosion.
[0156] Figure 15 This is the temperature universality test result of the method of polymetallic oxyacid anion cluster in situ alleviating metal chloride corrosion. Figure 15 It can be seen that MoO4 2- The increase of concentration is beneficial to the long-term stability of the electrode, and in MoO4 2-When the concentration is the same, temperature changes have no significant effect on the electrode stability time in the accelerated aging test, which proves the temperature universality of the method of polymetallic oxoacid anion clusters to alleviate metal chloride corrosion in situ.
[0157] 4. Molybdenum concentration universality test:
[0158] The three-electrode system of each electrolysis system in Example 4 and Comparative Example 1 was connected to the electrochemical workstation to construct a complete voltage and current loop to build an electrochemical corrosion research system. Accelerated aging experiments were carried out using electrolytes with different molybdenum concentrations: the constant current parameter of the chronopotentiometry was set to 1A, and the accelerated aging test was carried out to record the change of the system potential over time. Figure 16 The experimental results shown in FIG1 indicate that the introduction of molybdenum oxyacid ions at different concentrations has an improving effect on electrode stability, and the improving effect increases with the increase of molybdenum concentration.
[0159] Figure 17 Based on the polymolybdate ion conversion equation and conversion equilibrium constant, the relationship between the existence form of molybdate ions and the relative percentage content in response to the solution pH is calculated. Specifically, when the molybdenum concentration is 0.4 mol / L (calculated as molybdenum atoms), the response effect of the molybdenum existence form on pH is shown in the upper left figure. When the pH is greater than 7, molybdenum is almost completely converted to MoO4 in neutral and alkaline solutions. 2- It exists in the form of Mo7O, with a pH of about 5.5 24 6- The percentage of Mo7O 24 6- Gradually transforms into HMo7O 24 5- The transition state reaches its peak at around pH = 4. When the pH drops to 2, molybdenum is almost completely converted to Mo8O 26 4- The upper right figure shows Mo7O 24 6- With HMo7O 24 5- Merged into the same form, it can be seen from the figure that Mo7O 24 6- It begins to form at pH=7 and reaches its peak at around pH=5. Figure 17 The lower left and right figures show the distribution of molybdate and polymolybdate ion concentrations with respect to pH, and the trend of each ion change is the same as the two figures above. Figure 12 、 Figure 13 and Figure 17Changes in the total molybdenum concentration will not affect the range of polymolybdate formation and the ratio of various species. Molybdenum solutions with different concentrations all have the characteristics of polymerization under local acidic conditions, which illustrates the universality of the method of in situ alleviation of metal chloride corrosion by polymetallic oxyacid anion clusters for solutions with different molybdenum concentrations.
[0160] 6. Stability test of electrolyte used in alkaline anion exchange membrane electrolytic cell:
[0161] The alkaline anion exchange membrane electrolytic cells in Example 6 and Comparative Example 5 were respectively connected to an electrochemical workstation to form a complete voltage and current loop. Stability tests were performed using chronopotentiometry, with the constant current parameter set to 1A.
[0162] Figure 18 Stability testing results for an alkaline anion exchange membrane electrolyzer with nickel as the working electrode in electrolytes S8 (molybdenum metal oxoate cluster electrolyte) and D5. In electrolyte D5, electrode corrosion and failure occurred after 12,000 seconds (3.3 hours) of operation. However, in electrolyte S8, the cell maintained stable operation for over 800 hours, demonstrating that the polymetallic oxoate anion cluster in-situ method for mitigating metal chloride corrosion can be successfully applied to alkaline anion exchange membrane electrolyzers.
[0163] 7. Effect of electrolyte on corrosion protection of catalyst electrodes in electrochemical reactions in chlorine-containing electrolytes
[0164] Figure 19 It is the effect of molybdenum metal oxyacid anion cluster on the chlorine corrosion resistance of iron-doped nickel hydroxide. The iron-doped nickel hydroxide of the commonly used oxygen evolution reaction catalyst is loaded on the nickel metal electrode, and a three-electrode system as in Example 1 and Comparative Example 1 is constructed (only the nickel metal electrode loaded with iron-doped nickel hydroxide replaces the nickel metal electrode in Example 1 and Comparative Example 1, and the other electrolysis systems are the same as in Example 1 and Comparative Example 1), and accelerated aging tests are carried out in electrolyte D1 and electrolyte S1, respectively. The electrolyte and ambient temperature are room temperature (20°C). The constant current parameter of the chronopotentiometry is set to 1A. Among them, the method for loading iron-doped nickel hydroxide on the nickel metal electrode is not limited. In this experimental example, a hydrothermal method is used to prepare iron-doped nickel hydroxide on a foam nickel metal electrode (reference: Nature Communications volume 14, Article number: 1686 (2023)).
[0165] Depend on Figure 19 As can be seen, the electrode in electrolyte D1 suffered severe chlorine corrosion and failed after about one hour, while it could operate stably for more than three hours in electrolyte S1. This demonstrates that the in-situ metal chloride corrosion mitigation method provided by the present invention using polymetallic oxoacid anion clusters can be successfully applied to corrosion protection of iron-doped nickel hydroxide catalysts.
[0166] Figure 20 Based on the test results of the accelerated aging test in which the nickel metal electrode loaded with iron-doped nickel hydroxide replaced the nickel metal electrode in Example 1 and Comparative Example 1, the potential decay rate (DV) and performance decay rate (also known as activity decay rate, DA) of iron-doped nickel hydroxide in electrolyte D1 and electrolyte S1 were calculated respectively; the calculation formula is:
[0167]
[0168] and The voltage averages during the accelerated aging test (CP test) were taken during the initial 10% of t and the final 10% of t within the test time t to eliminate fluctuations during long-term operation. (Calculation formula reference: Nature Communications volume 14, Article number: 3607(2023)). It can be seen that the potential decay rate and performance decay rate of iron-doped nickel hydroxide in electrolyte S1 are lower than the corresponding values in electrolyte D1.
[0169] The embodiment of the present invention provides a method for in-situ mitigation of metal chloride corrosion by polymetallic oxyacid anion clusters. This is an in-situ corrosion prevention method developed based on the phenomenon of different pH between the bulk and interface of a solution system. During the metal corrosion process under open circuit potential or applied anodic potential, the local pH of the metal surface is reduced, and polymetallic oxyacid clusters are induced in situ. Through the specific chemical adsorption of the polymetallic oxyacid anion clusters on the metal electrode surface, the reaction with Cl - The electrostatic repulsion and steric hindrance effect between the two reduce the interfacial Cl - The present invention can utilize the chemical corrosion and electrochemical corrosion process of metal in seawater to consume OH - Based on the properties of the metal, a method was developed to induce the in-situ formation of polymetallic oxyacid anion clusters on the metal surface by changing the microenvironmental pH at the interface to achieve metal corrosion protection in seawater. This method does not require changing the metal electrode structure and can achieve the corresponding anti-corrosion effect of the microenvironmental pH at the interface in bulk solutions of different pH values, with good applicability over a wide pH range. Target scenarios include corrosion protection of catalyst electrodes in electrochemical reactions in chlorine-containing electrolytes, such as corrosion protection of oxygen evolution reaction catalysts and chlorine evolution reaction catalysts and substrates.
[0170] The metal electrode in the present invention resists Cl - The corrosion strategy focuses on the anti-corrosion process of the electrode surface under the in-situ pH environment change process. The chemical corrosion and electrochemical corrosion process of metal electrodes are accompanied by OH - At the same time, the high current density seawater electrolysis process is also accompanied by OH- The consumption of the electrode in situ will cause a significant change in the above process. The polymetallic oxoacid anion cluster structure described in this patent has a reversible response relationship with pH.
[0171] Among them, based on the response change relationship between the polymetallic oxoacid anion and the environmental pH, it is shown that OH occurs during the electrolysis of the chlorine-containing solution (or seawater). - Consumption, the electrode surface will undergo in-situ pH changes, the in-situ low pH environment induces the in-situ polymerization of molybdate monomers on the electrode surface to form polymolybdate anion clusters, which will affect the Cl in the solution. - The corrosion protection plays an effective role, and with the increase of the seawater electrolysis current density, the change of in-situ pH and the polymerization degree of polymetallic oxoacid anions are correspondingly enhanced (such as Figure 11 ).
[0172] The metal oxyacid anions represented by molybdate in the present invention have the characteristics of polymerizing into metal oxyacid anion clusters, such as MoO4 2- The monomer can be polymerized into Mo7O 24 6- or octamolybdate Mo8O 26 4- , and there is a corresponding reversible response relationship between the existence form of the molybdenum polymer ion and the solution pH (such as Figure 12 、 Figure 13 The formed polymetallic oxoacid anion cluster has a remarkable and excellent effect in resisting chloride ion corrosion.
[0173] Unless otherwise specified, the term "about" herein means that the error is within a range of ±2%. For example, "about 100" is actually 100 ± 2% × 100. "Normal temperature" or "room temperature" herein, unless otherwise specified, means approximately 20-30°C. "Between" herein includes the number itself; for example, "between 2-3" includes both the endpoints 2 and 3.
[0174] While the embodiments of the present invention have been described in detail above with reference to the accompanying drawings, the present invention is not limited to the embodiments described above. Various modifications may be made within the scope of knowledge possessed by a person skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof may be combined with one another unless there is a conflict.
Claims
1. Metal oxygen-containing acid ions are used to inhibit the chemical or electrochemical corrosion of metals by chloride-containing solutions.
2. The use according to claim 1, characterized in that The chlorine-containing solution contains Cl - , Cl in chlorine-containing solution - The concentration of chlorine is 0.1-5 mol / L, and / or the pH range of the chlorine-containing solution is 0-14; Preferably, the metal element in the metal oxyacid ions includes at least one of chromium, molybdenum or tungsten.
3. The use according to claim 1, characterized in that A corrosion inhibitor containing metal oxygen acid radical ions is added to a chlorine-containing solution to protect metal electrodes or metal substrates during electrochemical corrosion or chemical corrosion; Preferably, the metal oxygen acid radical ions are used in the electrolyte of seawater electrolysis to protect metal electrodes from corrosion; Preferably, the protected or guarded metal includes at least one of Ni, Mo, Fe, Co, Ti or Au.
4. The use according to claim 1, characterized in that The corrosion inhibitor containing metal oxygen acid radical ions is added to the chlorine-containing solution to protect the metal electrode or metal substrate in electrochemical corrosion or chemical corrosion; wherein the raw materials of the chlorine-containing solution include Cl - At least one of seawater, simulated seawater, industrial electrolyte, industrial wastewater or tap water; Preferably, the electrochemical reaction comprises a seawater electrolysis reaction; Preferably, the metal oxygen-containing acid radical ions are used for corrosion protection of oxygen evolution reaction catalyst layered double metal hydroxides, corrosion protection of oxygen evolution reaction catalysts, corrosion protection of chlorine evolution reaction catalysts, corrosion protection of oxygen evolution reaction metal substrates, corrosion protection of chlorine evolution reaction metal substrates or corrosion protection of alkaline anion exchange membrane electrolyzers.
5. An electrolyte capable of alleviating metal corrosion, characterized in that: The electrolyte includes chloride ions and at least one of metal oxyacid ions or polymetallic oxyacid anion clusters; Preferably, the metal elements in the metal oxo ions and the polymetallic oxo anion clusters are independently selected from at least one of chromium, molybdenum or tungsten; Preferably, the metal oxyacid ion includes at least one of molybdate, chromate or tungstate; and / or, the polymetallic oxyacid anion cluster includes at least one of heptamolybdate, octamolybdate, chromate, dichromate, heptotungstate, decatungstate and dodecatungstate; Preferably, in the electrolyte, the sum of the initial concentrations of the metal oxo ions and the polymetallic oxo anion clusters is 0.01-6 mol / L, calculated as metal atoms.
6. The electrolyte according to claim 5, characterized in that The electrolyte contains Cl - , Cl - The concentration of the electrolyte is 0.1-5 mol / L; and / or the pH range of the electrolyte is 0-14.
7. The electrolyte according to claim 5, characterized in that The raw materials for preparing the electrolyte include a corrosion inhibitor, and the corrosion inhibitor includes metal oxygen acid ions; Preferably, the corrosion inhibitor comprises at least one of molybdate, chromate or tungstate; Preferably, the molybdate includes at least one of sodium molybdate, potassium molybdate, ammonium molybdate or ammonium heptamolybdate; and / or, the chromate includes at least one of sodium chromate, potassium chromate, magnesium chromate or ammonium chromate; and / or, the tungstate includes at least one of sodium tungstate, potassium tungstate or ammonium tungstate.
8. The electrolyte according to claim 7, characterized in that The raw materials for preparing the electrolyte also include aqueous fluid; Preferably, the aqueous fluid comprises at least one of natural seawater, simulated seawater, industrial electrolyte, industrial wastewater or tap water; Preferably, the raw materials for preparing the electrolyte further include at least one of an alkaline substance or an electrolyte substance; Preferably, the electrolyte substance comprises a metal chloride; and / or the alkaline substance comprises at least one of sodium hydroxide or potassium hydroxide; Preferably, the metal chloride comprises at least one of sodium chloride or potassium chloride.
9. An electrolysis system, characterized in that: The electrolyte comprising the electrolyte according to any one of claims 5 to 8.
10. A method for alleviating corrosion of a metal electrode, characterized in that: The method comprises the following steps: placing a metal electrode in a chlorine-containing electrolyte for electrolysis, wherein the chlorine-containing electrolyte comprises the electrolyte according to any one of claims 5 to 8; Preferably, the temperature of the electrolyte is 10-90°C.
Citation Information
Patent Citations
Anti-incrustation corrosion inhibitor for circulating water system with high concentration time and high chloride ion content
CN101759301A
Cited By
Electrolyte additive for improving water electrolysis reaction performance, electrolyte, electrolyte solution, and method for improving water electrolysis reaction performance
WO2025228263A1